Direct amplification of reference samples with Globalfiler® PCR Amplification Kit. (December 2015) - Gouveia, N.; Brito, P.; Serra, A.; Balsa, F.; Andrade, L.; Bento, M.São; Cunha, P.; Bogas, V.; Lopes, V.; Porto, M.J.
Abstract: The GlobalFiler ® PCR Amplification system uses 6-dye fluorescent chemistry to enable multiplexing of 21 autosomal STRs, 1 Y-STR, 1 Y-indel and the sex-determining marker amelogenin. Validation studies were conducted to assess the performance of the GlobalFiler ® casework kit for typing reference samples through a direct amplification. The findings support that the GlobalFiler ® PCR Amplification Kit produces reliable results from blood and buccal reference DNA samples.